Long-Term Feeding with Curcumin Affects the Growth, Antioxidant Capacity, Immune Status, Tissue Histoarchitecture, Immune Expression of Proinflammatory Cytokines, and Apoptosis Indicators in Nile Tilapia, Oreochromis niloticus - Shimaa A. Amer; Doaa A. El-Araby; Haitham Tartor; Mahmoud Farahat; Nehal I. A. Goda; Mohamed F. M. Farag; Esraa M. Fahmy; Aziza M. Hassan; Mohamed F. Abo El-Maati; Ali Osman (MDPI AG, 2022)
The impact of dietary curcumin (CUR) on the growth, antioxidant activity, histomorphology of certain organs, proinflammatory cytokine production, and immune status of Oreochromis niloticus was evaluated. The fingerlings (n = 225, 41.60 ± 0.09 g/fish) were randomly allotted into five experimental groups in triplicate. Fish were fed basal diets complemented with 0, 200, 400, 600, or 800 mg curcumin/kg diet (CUR0, CUR200, CUR400, CUR600, and CUR800, respectively) for 10 weeks. An increase in fish growth was reported in the CUR200 and CUR400 groups. The feed conversion ratio was enhanced by 15% in the CUR400 group. Fish body protein content was increased in the CUR600 group (p ≤ 0.01). Body fat was decreased, and ash content was increased by CUR supplementation in a level-related way (p < 0.05). The villus height was increased in the CUR400 and CUR600 groups. The villus width was increased by CUR supplementation, with the best result found in the CUR600 group. The liver of CUR-fed fish displayed comparatively normal hepatocytes. TNF-α and caspase-3 were significantly upregulated by dietary CUR in a level-related way. The serum catalase activity and GSH level were increased in CUR200 and CUR400 groups. Curcumin supplementation boosted the serum SOD activity and reduced the MDA level. IL10 and IgM levels were increased in the CUR200 and CUR400 groups. Lysozyme activity was increased in the CUR200-400 groups. Serum complement 3 level was increased in the CUR400 group. The percentage survival of O. niloticus challenged with Aeromonas hydrophila was highest in the CUR200-CUR600 groups (100%) and decreased in the CUR800 group (80%). This study concluded that CUR could be added to Nile tilapia diets up to 400 mg·kg−1 to achieve better growth, antioxidant capacity, immune response, and intestinal histology. Long feeding periods on high levels of CUR (600 and 800 mg·kg−1) stimulate inflammatory reactions in fish tissues.